Interest Profile of Infant’s Mother on Receiving Multiple Injection Immunization - Pratiwi, Setyo Endah; Sriatmi, Ayun; Agushybana, Farid (Journal of Maternal and Child Health, 2023)
Background: Multiple injections are giving more than one type of immunization in one visit which aims to protect children earlier in vulnerable times, immunization visits will be fewer so that it will make it easier for children with difficult or limited access to health services, people Older people do not need to come to health facilities repeatedly, increase efficiency for health service providers, and avoid missed opportunities. This study aimed to determine a significant relationship between the independent variables, namely knowledge, perceived vulnerability, perceived severity, perceived benefits, perceived barriers, and family support with the dependent variable, namely the infant's mother's interest in receiving multiple injection immunization. Subjects and Method: This study was a cross sectional study. A sample of 407 infant's mothers were selected in this study. The dependent variable was namely the infant's mother's interest in receiving multiple injection immunization. The independent variable were namely knowledge, perceived vulnerability, perceived severity, perceived benefits, perceived barriers, and family support. The data were analyzed by SPSS application. Results: The average score of correct answers related to the knowledge of mothers who are interested (Mean= 7.32; SD= 1.23) greater than mothers who are not interested (Mean= 5.23; SD= 0.87). The average score of correct answers related to the perceived vulnerability of mothers who are interested (Mean= 23.45; SD= 4.61) greater than mothers who are not interested (Mean= 10.39; SD= 0.87). The average score of correct answers related to the perceived severity of mothers who are interested in receiving multiple injection cages (Mean= 9.70; SD= 4.42) greater than mothers who are not interested (Mean= 7.45; SD= 0.92). The average score of correct answers related to the perceived benefit of mothers who are interested (Mean= 16.74; SD= 3.38) greater than mothers who are not interested (Mean= 7.32; SD= 0.7o). The average score of correct answers related to the perceived barrier of mothers who are interested (Mean= 23.18; SD= 4.31) greater than mothers who are not interested (Mean= 11.78; SD= 1.17). The average score of correct answers related to the family support of mothers who are interested in receiving multiple injection cages (Mean= 28.89; SD= 5.16) greater than mothers who are not interested (Mean= 16.08; SD= 1.38). All these results were significant statistic (p<0.001). Conclusion: There is a significant influence between knowledge, perceived vulnerability, perceived severity, perceived benefits, perceived barriers, and family support with the infant's mother's interest in receiving multiple injection immunization. Keywords: multiple injections, immunization, infants mother. Correspondence: Setyo Endah Pratiwi. Department of Public Health, Postgraduate School, Universitas Diponegoro. Jl. Prof. Sudarto No. 13 Tembalang, Semarang 50275, Central Java. Email: endahsulthan13@gmail.com. Mobile: +62 822-2137-5962